A review of β-cyclodextrin-based catalysts system in the chemical fixation of carbon dioxide - Sara Payamifar; Ahmad Poursattar Marjani (Journal of CO2 Utilization)
Carbon fixation is a vital chemical and biological methodology where carbon dioxide (CO2) from the environment is altered into organic materials. This process creates the basis of the carbon cycle. It plays a significant role in maintaining Earth’s life and adjusting its climate. Cyclic carbonates are best known as multipurpose compounds and have broad utility in pharmaceutical construction and producing multiple fine chemicals. The cycloaddition of CO2 and epoxide to create cyclic carbonates is regarded as one of the most hopeful CO2 transformations due to its completely non-toxicity, economical, and much atomic economy technical routes for the employment of CO2. However, utilizing the highly chemically stable CO2 requires high bond cleavage energy of the CO bond. Therefore, it is crucial to design and develop appropriate catalysts for the chemical fixation of CO2. Recently, employing β-cyclodextrin (β-CD) as a catalyst has dramatically improved due to unique properties like low-price, available, non-toxic, stable, biodegradable, renewable, green, eco-friendly, and the ability to create inclusion complexes. This investigation studies the preparation of cyclic carbonates utilizing a β-CD-based catalyst system via CO2 molecular, which profoundly analyzes the research advancement of recent years. This review helps scientists to use contemporary improvements and, therefore, may furnish several beneficial visions for future studies on the construction of cyclic carbonates utilizing CO2 as the feedstock. It will deliver a helpful reference and directory for researchers to progress better.